Work environment analysis to improve employee performance - Dullah, Mohammad; Limgiani, Limgiani; Suwardi, Lukas Alfaris (CV. Bimbingan Belajar Assyfa, 2023)
Working environmental conditions have a significant influence on employee performance. This research aims to analyze how the work environment at the East Java Cooperative and SME Training UPT Office affects employee performance. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participant observation, and documentation. The main informants consisted of 10 employees selected based on certain criteria. The research results show that a clean, bright, peaceful, and safe work environment, as well as office facilities such as air conditioning, Wi-Fi, and other important equipment, play a significant role in increasing employee motivation and performance. Apart from that, good working relationships between superiors and subordinates also make a positive contribution to performance. The implications of this research show that improving the physical and social work environment can improve employee performance significantly and sustainably.